Urban Planning and Development in Upper Canada - Stelter, Gilbert (Urban History Review / Revue d'histoire urbaine, 1980)
This paper describes the planning and development of the towns and cities of Upper Canada, the frontier region of British North America. Imperial officials consciously used towns as agencies for the settlement of this region, based on the British experience in Ireland and the American colonies. By the mid-nineteenth century, the colonial entrepôts had become ambitious commercial centres. While the social system was reflected in a conservative approach to local government, for example, the physical artifacts closely resembled their counterparts in the United States.